Penggunaan Media Pembelajaran Audio Visual Dalam Meningkatkan Keterampilan Berfikir Kritis Siswa Dalam Pembelajaran Pai Di Sekolah Dasar - Mohammad Bahrul Hidayat; Natsir, Muhammad (Pekerti: Journal Pendidikan Islam dan Budi Pekerti, 2025)
In the era of modern digital development, the use of learning media such as audio-visual media is no longer common. These media provide a different learning impression because they provide a new, interesting and easy-to-understand impression for students. In the world of learning, the use of Audiovisual media is very important. This study uses a quantitative descriptive method with a single group pretest-posttest design. The subjects of this study were all 20 fifth-grade students of SDN Bulak Baru Jepara, who were also used as research samples. Data collection was carried out by testing students' abilities in using audio-visual materials in Islamic Religious Education (PAI). Data analysis used statistical techniques, which included normality tests, validity tests, and t-tests. Based on the results of the analysis, it shows that audio-visual media can improve students' critical thinking skills in PAI subjects with pretest results of 69.00 and posttest 82.35 t count ((-7.045> t table 1.729)), so the conclusion is Ha is accepted. Thus, it can be concluded that the use of audiovisual media can have a positive impact on the critical thinking skills of fifth-grade students of SDN Bulak Baru Jepara.